2016
DOI: 10.1039/c6cp04454a
|View full text |Cite
|
Sign up to set email alerts
|

Surface directed reversible imidazole ligation to nickel(ii) octaethylporphyrin at the solution/solid interface: a single molecule level study

Abstract: Scanning tunneling microscopy (STM) is used to study for the first time the reversible binding of imidazole (Im) and nickel(ii) octaethylporphyrin (NiOEP) supported on highly oriented pyrolytic graphite (HOPG) at the phenyloctane/NiOEP/HOPG interface at 25 °C. The ligation of Im to the NiOEP receptor while not observed in fluid solution is readily realized at the solution/HOPG interface. The coordination process scales with increasing Im concentration and can be effectively modeled by the Langmuir isotherm. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 62 publications
0
41
0
Order By: Relevance
“…PDFT calculations of not porphyrins but porphyrin-based molecules are also studied in the literature. For example, Zhang et al studied the adsorption of Ni(Salophen) molecule on Au(111) surface using vdW-DFT functionals and determined the adsorption energy to be 2.74 eV which is about 2/3 of the adsorption energy of similar porphyrin [96,106] molecules on Au(111). Gurdal et al studied the adsorption of pyrphyrin molecules on Au(111) [107] and Ag (111) [108] surfaces using various GGA and vdW-GGA functionals.…”
Section: Conformational Studies Of Non-meso-substituted Porphyrins Onmentioning
confidence: 99%
See 2 more Smart Citations
“…PDFT calculations of not porphyrins but porphyrin-based molecules are also studied in the literature. For example, Zhang et al studied the adsorption of Ni(Salophen) molecule on Au(111) surface using vdW-DFT functionals and determined the adsorption energy to be 2.74 eV which is about 2/3 of the adsorption energy of similar porphyrin [96,106] molecules on Au(111). Gurdal et al studied the adsorption of pyrphyrin molecules on Au(111) [107] and Ag (111) [108] surfaces using various GGA and vdW-GGA functionals.…”
Section: Conformational Studies Of Non-meso-substituted Porphyrins Onmentioning
confidence: 99%
“…Nandi et al [106], used PDFT simulations with vdW-DF [43,48] functional to understand the binding mechanism of imidazole (Im) ligand to Ni-octaethylporphyrin (NiOEP) bound on HOPG surface. Using STM, solution-spectroscopy, and molecular DFT calculations the authors reported that Im ligand does not bind to NiOEP in solution or in gas-phase but does bind when NiOEP is on the HOPG surface.…”
Section: Ligand-porphyrin Reactions On Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…, , ). Recent publications have been reporting studies about the dynamic behaviour of porphyrins, in particular, conformational manipulations using STM (Zhao et al ., ; Kumagai et al ., ; Nandi et al ., ; Lensen et al ., ) and a recent review paper highlights some of the experiments that involved porphyrin manipulation using STM (Auwarter et al ., ). Most of them, are related to porphryins conformational switching in response to external inputs like temperature, light, atomic force or current.…”
Section: Introductionmentioning
confidence: 99%
“…These distortions also influence the conductivity of the porphyrins which is an important property for the design of organic electronic systems (Wolfle et al, 2008;Ferreira et al 2014Ferreira et al , 2011Ferreira et al , 2013. Recent publications have been reporting studies about the dynamic behaviour of porphyrins, in particular, conformational manipulations using STM (Zhao et al, 2013;Kumagai et al, 2014;Nandi et al, 2016;Lensen et al, 2012) and a recent review paper highlights some of the experiments that involved porphyrin manipulation using STM (Auwarter et al, 2015). Most of them, are related to porphryins conformational switching in response to external inputs like temperature, light, atomic force or current.…”
Section: Introductionmentioning
confidence: 99%